Student conduct programs' utilization of learning outcomes to measure educational sanctions: a phenomenological analysis - Draper Davis, Julie A., author; Kuk, Linda, advisor; Chesson, Craig, committee member; Miller, Lisa, committee member; Sheafor, Brad, committee member (Colorado State University. Libraries, 2014)
This phenomenological study explored the experiences of student conduct administrators who measure student learning when educational sanctions are assigned. The lived experiences of the participants were explored through the following research questions: (1) What educational sanctions do student conduct administrators assign in the student conduct process? (2) What learning outcomes do student conduct administrators utilize for educational sanctions? (3) How do student conduct administrators measure learning for students who participate in educational sanctions? (4) What challenges do student conduct administrators face when measuring learning for students who participate in educational sanctions? (5) How do student conduct administrators communicate the results of student learning to their campus community? The researcher conducted semi-structured interviews with eleven student conduct administrators representing large public research institutions in the United States. Using the interpretative phenomenological approach, four themes emerged during the analysis of the data. The lived-experience of the participants was characterized by: (1) culture of assessment, (2) measuring learning, (3) alcohol education, and (4) external factors. The data suggested that the essence of the lived experience for student conduct administrators is that measuring learning for students who participate in educational sanctions is challenging.
Keywords: educational sanctions; assessment; learning outcomes; student affairs; student conduct